Socioeconomic efficiency of neonatal screening for spinal muscular atrophy in the Russian Federation - I. A. Komarov; A. R. Malakhova; T. P. Vasilyeva; E. Yu. Shukan; O. Yu. Aleksandrova; R. A. Zinchenko; A. V. Polyakov; S. S. Nikitin; E. Yu. Sapego; S. I. Kutsev (Нервно-мышечные болезни)
Background. Spinal muscular atrophy (SMA) is a severe rare disease that has been widely discussed in recent years. Achievements in etiopathogenetic therapy and the social significance of the disease (child population, high mortality), the cost of treatment attracted the attention of the public and the goverment, which, among other things, led to the formation of a separate area with the creation of a fund to finance the treatment of patients with orphan diseases.Aim. To conduct an analysis of the socio-economic efficiency of mass neonatal screening for SMA in the Russian Federation.Materials and methods. A survey of patients (their parents) and doctors was conducted. The current clinical guidelines and the standard of medical care for children with SMA were studied. The cost of medicines is taken from the State Register of Maximum Selling Prices. If the drug is not included in the List of Vital Essential and Necessary Drugs, cost information from the procurement data is used.Results. The socioeconomic burden of SMA on identified patients was about 3,994,289,548 rubles per year prior to screening. The very introduction of mass neonatal screening will amount to about 679,224,000 rubles in year. At the same time, a disease detected in a timely manner due to neonatal screening and timely prescribed effective treatment can lead to a reduction in the cost of specialized and palliative care by 54,073,271 rubles, direct non-medical costs by 88,137,423 rubles, and indirect costs by 154,197,900 rubles per year, which together is more than 7 % of the calculated burden of SMA.Conclusion. The introduction of mass screening will lead to the fact that the number of annually detected patients will increase from current values to the actual value of the prevalence when registering patients with milder forms of SMA. The need for drug supply with drugs and medical care in general will increase. At the same time, children diagnosed with SMA will not die in the early years of life, their survival rate, life expectancy will increase, the quality of life will improve, infant mortality will decrease, which is the main task of neonatal screening and one of the goals of the National Healthcare Project.